Profile of The National Level 1 Physical Coach in 2022 (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2022)
This study aims to determine the profile of the national level 1 physical trainer in 2022 who has an important role in athlete achievement in the world of achievement sports. This research was conducted on training participants who have passed the National Accreditation Institute for Sports (Lankor) in collaboration with STOK Bina Guna. The method used is descriptive with survey data collection techniques. From the data obtained, it can be concluded that the profile of the national level 1 physical trainer in 2022 when viewed from the age side is still very productive, in terms of the licenses they have are already qualified as trainers even though some trainers are considered to be very beginners, in terms of the length of time they train, they are considered physical trainers. The national level 1 has experience that can be applied when training, and in terms of educational background it is still dominated by sports graduates.